Childhood Maltreatment History, Posttraumatic Relational Sequelae, and Prenatal Care Utilization. Issue 4 (17th June 2013) - Bell, Sue Anne; Seng, Julia
ABSTRACT Objective To test the hypothesis that childhood maltreatment history would be associated with inadequate prenatal care utilization. Design A post‐hoc analysis of a prospective cohort study of the effects of post traumatic stress disorder (PTSD) on pregnancy outcomes. Setting Recruitment took place via prenatal clinics from three academic health systems in southeast Michigan. Participants This analysis included 467 diverse, nulliparous, English‐speaking adult women expecting their first infants. Methods Data were gathered from structured telephone interviews at two time points in pregnancy and from prenatal medical records. Results Contrary to our hypothesis, history of childhood maltreatment was associated with better likelihood of using adequate prenatal care. Risk for inadequate prenatal care occurred in association with the posttraumatic stress and interpersonal sensitivity that can result from maltreatment, with low alliance with the maternity care provider, and with public insurance coverage. Prior mental health treatment was associated with using adequate prenatal care. Conclusion When childhood maltreatment survivors were resilient or had used mental health treatment, they were more likely to utilize adequate prenatal care. The maternity care relationship or service delivery model (e.g., no continuity of care) as well as structural factors may adversely affect utilization among PTSD‐affected survivors. Since inadequate care was associated with adverse outcomes, further studies of these modifiable factors are warranted.